Stabilization of low-valence transition metal towards advanced catalytic effects on the hydrogen storage performance of magnesium hydride - Jian Zhang; Shuai Yan; Guanglin Xia; Xiaojie Zhou; Xianzheng Lu; Linping Yu; Xuebin Yu; Ping Peng (Journal of Magnesium and Alloys, 2021)
Magnesium hydride (MgH2) has been widely regarded as a potential hydrogen storage material owing to its high gravimetric and volumetric capacity. Its sluggish kinetics and high activation energy barrier, however, severely limit its practical application. Transition metal oxides (TMOs) have been extensively used as catalysts to improve the hydrogen storage performance of MgH2, but the low-valence transition metal (TM) ions, resulting from the reduction of TMOs accompanied by the formation of inactive MgO, have been demonstrated to be the most effective components. Herein, we theoretically and experimentally confirm that the doping of low-valence TMs into MgO could effectively weaken the Mg-H bonds and decrease the energy required for hydrogen desorption from MgH2, leading to superior catalytic activity compared to both TMOs and MgO. In particular, the apparent activation energy for the dehydrogenation of Mg(Nb)O-catalyzed MgH2 could be reduced to only 84.1 kJ mol-1, and the reversible capacity could reach around 7 wt.% after 5 cycles with a capacity retention of 96%. Detailed theoretical calculations confirm that the remarkable orbital hybridization between Mg(Nb)O and MgH2 promotes charge transfer from MgO to the MgH2 monomer, resulting in significantly weakened stability of MgH2, which could effectively enhance its hydrogen storage performance.